KEMAMPUAN INFORMASI AKUNTANSI DALAM MEMPREDIKSI PERINGKAT OBLIGASI - Angga Wisesa Cokro Priambodo (2017)
his study was conducted to test the effect of variable Profitability Company Size and Leverage on Bond Ratings on all companies listed on the Stock Exchange from 2014 to 2015. The population in this study a number of 37 companies selling bonds and ranked by PEFINDO. Samples were obtained in this study, totaling 26 companies selected using purposive sampling method of determining sempel based on criteria determined that the financial statements ended on December 31, a company that uses the rupiah currency, and listed on the Indonesia Stock Exchange (BEI) in observational studies. The analysis technique used is the logistic regression models include tests overall fit test, test the coefficient of determination, test of Hosmer and Lemeshow's goodness of fit test, test parsialdan hypothesis testing using t-statistic with a probability level of 5%. The results of this study showed that significantly influence the profitability of Bond Ratings, Company Size significant negative effect on Bond Ratings and Leverage not significant effect on bond rating. The author suggested to investors and readers to pay attention to other factors that influence bond rating. Both variables Profitability Company Size and Leverage is NOT significantly due from the whole sample in ANY variable few that affects bond ratings.